Mortality and comorbidities among teaching professionals: A cross-sectional study in Colombia - Daniela Sánchez-Santiesteban; Hernando Bayona-Rodríguez; Giancarlo Buitrago (PLoS ONE, 2026)
Background Teachers play a critical role in social and economic development, yet evidence on their health outcomes in Latin America remains scarce. In Colombia, teachers are generally classified in occupational risk level 1, a category considered to have minimal hazards. This study aimed to describe and compare mortality and comorbidities among teachers and non-teachers in the same risk category, and to explore differences across educational levels within the teaching profession. Methods We conducted a retrospective cohort study using four linked national administrative databases in 2017. Adults affiliated to the contributory health insurance scheme and classified under occupational risk level 1 were included. Teachers were identified and stratified by educational level. Outcomes included one-year all-cause mortality and prevalence of mental health and hearing disorders. Multivariable logistic regression models adjusted for sociodemographic and clinical covariates were used to estimate associations. Results A total of 4,256,719 individuals were included, of whom 353,985 (8.3%) were teachers. Teachers were older (mean age 40.1 vs 36.4 years) and more frequently female (69% vs 60%) than non-teachers. The one-year mortality proportion was higher among teachers (0.14%) than non-teachers (0.11%). After adjustment, teaching was associated with a 15% higher risk of mortality (OR: 1.15, 95% CI: 1.03–1.28). No significant associations were found for mental health (OR: 0.98, 95% CI: 0.96–1.01) or hearing disorders (OR: 0.97, 95% CI: 0.92–1.02). Subgroup analyses showed the highest mortality proportions among teachers in technical and technological education. Conclusions Despite being classified in the lowest occupational risk level, private-sector teachers in Colombia exhibited higher mortality compared with other workers in the same group. Differences in mental health and hearing disorders were not significant. These findings highlight the need to strengthen surveillance, prevention, and protection strategies tailored to teachers, recognizing them as a priority population within occupational health and education policies.